Kimbap as a Postcolonial Arena: Culinary Contestation and the Repositioning of Korean Cultural Identity towards Japan - Faris Asyraf Widiantoro; Adi Kristina Wulandari (Dinasti International Journal of Education Management And Social Science, 2025)
The Hallyu phenomenon has increased global interest in Korean cuisine, including kimbap. However, the history of kimbap raises debates over its origins, whether it is a Joseon tradition (Bokssam) or an adaptation of Japanese sushi during the colonial period. This article analyzes how kimbap became a symbol of resistance to the repositioning of postcolonial Korean cultural identity. Using a qualitative method with a literature review, this study shows that South Korea's attempt to separate kimbap from sushi is a cultural strategy to assert autonomy and uniqueness. Kimbap functions as a "symbolic resistance" to Japanese culinary heritage, with Korea creating a narrative of authenticity. This analysis is supported by Stuart Hall's theory of identity that views identity as a fluid entity shaped by historical and cultural relations, as well as Homi Bhabha's concepts of hybridity and "Third Space" that explain the negotiation of new identities amid colonial influence. Kimbap becomes a dynamic manifestation